Small Bodies in Planetary Systems - Mann, Ingrid (Springer, 2017)
1 From Protoplanetary Disks to Planetary Disks: Gas Dispersal and Dust Growth. 2. Dynamics of Small Bodies in Planetary Systems. 3. Asteroids and Their Collisional Disruption. 4. On the Strength and Disruption Mechanisms of Small Bodies in the Solar System...